The Little, Brown Handbook - Fowler, H. Ramsey and Aaron, Jane E. (Glenview Scott, Foresman and Company, 1989)
This book serves as a text and as a quick-reference book for writing. It is a basic resource for English composition, grammar, and usage.
Keywords: Writing